STUDY OF A SILICON POWER DIODE USING A TIME DEPENDENT HYDRODYNAMIC MODEL (Sciences & Technology. A, exactes sciences, 2003)
A one-dimensional device simulator based on the hydrodynamic model is developed for the simulation and analysis of high voltage ambipolar devices. This simulator has the capability for both self-consistent transient  and steady state regime study. The discretization scheme used in the algorithm shows good numerical stability and accuracy.A transient simulation study is carried out on a PIN diode.  Information about electrical potential, electron and holes concentration, carriers temperatures, average velocities, considering the transient response to a high voltage, shows this simulator  quite a good tool to study power devices in futures trends. While no significant differences appear between our results and drift diffusion model ones, for the quiescent state, it is not the case for the transient regime. Moreover, our model does not handle  some strong simplification hypothesis;  for instance  it is pointed out that carrier explicit acceleration term can not be  dodged so easily, as reported before, for an accurate transient study.